2022
DOI: 10.1039/d2ob00906d
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-controlled Rh(iii)-catalyzed regiodivergent annulation towards fused and spiro benzimidazoles

Abstract: Rh(III)-catalyzed cascade C-H activation and cyclization of 2-aryl benzimidazoles with maleimides for the synthesis of benzimidazole-fused isoquinolines and benzimidazole spiro isoindoles is reported. The switchable selectivity in the formation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In 2022, Huang et al reported a 2-arylbenzimidazole 172 directed spirocyclization using a Rh-catalyst in the presence of AgOAc and AcOH in acetonitrile medium at 100 °C (Scheme 43). 38 Several substituents on the maleimide as well as on the benzimidazole have been tested for the sake of generalization and 19–74% yields of the spirocycles 173 were isolated.…”
Section: Heterocycle Directed Spirocyclizationmentioning
confidence: 99%
“…In 2022, Huang et al reported a 2-arylbenzimidazole 172 directed spirocyclization using a Rh-catalyst in the presence of AgOAc and AcOH in acetonitrile medium at 100 °C (Scheme 43). 38 Several substituents on the maleimide as well as on the benzimidazole have been tested for the sake of generalization and 19–74% yields of the spirocycles 173 were isolated.…”
Section: Heterocycle Directed Spirocyclizationmentioning
confidence: 99%